2015
DOI: 10.1039/c4cp04850d
|View full text |Cite
|
Sign up to set email alerts
|

Differences in single and aggregated nanoparticle plasmon spectroscopy

Abstract: Vibrational spectroscopy usually provides structural information averaged over many molecules. We report a larger peak position variation and reproducibly smaller FWHM of TERS spectra compared to SERS spectra indicating that the number of molecules excited in a TERS experiment is extremely low. Thus, orientational averaging effects are suppressed and micro ensembles are investigated. This is shown for a thiophenol molecule adsorbed on Au nanoplates and nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Bands detected within +/− 5 cm −1 were considered to be identical modes; such position variation always has to be accounted for and is a typical feature for small sample volumes, such as those used in TERS. Due to the high lateral resolution, only a few molecules are probed, and the statistical averaging of distinct band positions, such as in SERS, cannot be achieved 41 42 . It is apparent that several modes, represented by the light blue spots, were concurrently detected within the first 6 nm of the measured line.…”
Section: Resultsmentioning
confidence: 99%
“…Bands detected within +/− 5 cm −1 were considered to be identical modes; such position variation always has to be accounted for and is a typical feature for small sample volumes, such as those used in TERS. Due to the high lateral resolution, only a few molecules are probed, and the statistical averaging of distinct band positions, such as in SERS, cannot be achieved 41 42 . It is apparent that several modes, represented by the light blue spots, were concurrently detected within the first 6 nm of the measured line.…”
Section: Resultsmentioning
confidence: 99%
“…While usually higher enhancements can be achieved by clusters of particles, a single particle is the preferred geometry of a TERS probe, as this excludes complex interactions between many nanoparticles and would allow a tailored design regarding their resonance wavelength. The slight deviations from the usual uniformity are not unexpected and have been addressed in a recent study as effects of the very small sample volume in TERS [36].…”
Section: Ters Measurementsmentioning
confidence: 88%
“…For instance, the changes of adsorbate/analyte spectral features can be caused by any of the following reasons: molecule reorientation, conformational transitions, protonation of functional group, coadsorption of ions, and so forth . In a number of recent studies, it was found that an aggregation of metal nanoparticles also can induce the changes of SERS profile . These observations deserve a particular attention due to their connection to another burning issue of SERS spectroscopy, namely, to the hot spots phenomenon.…”
Section: Introductionmentioning
confidence: 99%